Diagnóstico de los niveles de mercurio en empleados y estudiantes de la Facultad de Odontología de la Universidad de Antioquia, 1999 - Escobar G., Juan Darío; Clara Eugenia, Clara Eugenia; Colimon G., Kahl; Molano Álvarez, Merly (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This descriptive study aims to lind the prevalence 01mercury intoxication among the students, and employees 01 the College 01Dentistry 01 the University 01Antioquia. This is the lirst in Colombia that evaluates students and laculty members and not just the auxiliary personnel. Mercury concentrations in 24-hour urine samples were co-/lected and measured with the atomic absorption procedure. The values were read lor absorbency and correlated with the Pearson 's correlation coefficient. The 192 samples showed concentrations lower than 30mmg. which is considered the intoxication merk, and 1.6% (3 samples) registerd values equal or higher than 15mmg. which is considered the impregnation limit lor the exposed working population. The highest registretion, 19mmg corresponded to one laculty member and 2 samples (Iaculty member and 9h semester student) showed values equal to 15mmg. All the positive results can not be aftributed totally to the clinical ection carried out in our institution. This lact introduces a conlusion variable, imposible to control, since it limits the conclusions. The results are attributed to changes in the handling 01mercury It's expected that this protocol and its methodology will be be replicated in other institutions.